Implications and Validity of the Association of Owners and Residents of Flats Units in Hotel Condominiums - Beatrix Tanjung; I Made Pria Dharsana (IHSA Institute, 2022)
Normatively, the implementation of flats with the concept of hotel condominiums (condotels) has not been regulated. However, in practice as in Decision No. 34/Pdt.G/2021/PN.Bgr it is stated that the implementation of condotels refers to the provisions of Law Number 20 of 2011 (Flats Law). In its management, condotels are managed by a hotel operator appointed by the developer based on an agreement with the condotel owner. This is a problem when a condotel is managed by a legal entity that is a hotel operator and not by the Association of Owners and Residents of Flats Units (PPPSRS) as mandated in the Flats Law. In this article, we will discuss, how the legal implications for the formation of condotel PPPSRS and the validity of the appointment of a hotel operator who replaces the authority of PPPSRS on Le'eminence condotels based on the Agreement for the Management and Operation of Condotel Unit Stacking Units based on Decision No. 34/Pdt.G/2021/PN.Bgr. This article concludes, PPPSRS on condotels still refers to the Flats Law whose arrangements are specifically regulated in PERMENPUPR 23/2018 which currently has changed to PERMENPUPR 14/2021 and the appointment of a hotel operator, namely PT EHS, which replaces the PPPSRS authority on the Le'Eminence condotel based on the Agreement for the Management and Operation of the Condotel Unit Flats is contrary to Article 1 number 22 of the Flats Law and Article 23 paragraph (3) of PERMENPUPR 23/2018.